Chronic myeloid leukemia on imatinib with recurrent sub-dural haemorrhage - Bhavani, Ambati; Dattatreya, Palanki Satya; Shyamala, Vinukonda (International Journal of Research in Medical Sciences, 2021)
Imatinib is an FDA approved first-line treatment for Philadelphia-positive CML. It is a selective tyrosine kinase inhibitor specifically targeting BCR-ABL, c-KIT, PDGFRA. It has been reported with low incidence of adverse effects and high tolerability, with haemorrhagic events being a rare complication. We report here a case of 51-year-old female patient with chronic myeloid leukemia who was on high dose imatinib experienced recurrent sub-dural haemorrhage. This case report emphasizes on the need to consider Sub dural haemorrhage as an unusual cause of headache associated with vomiting in a patient taking high dose of imatinib.